Member Self-Identification Toward Al-Ma'un Values as Organizational Identity: Case Study at PKU Muhammadiyah Yogyakarta Hospital - Djohantini, Siti Noordjannah; Mulkhan, Abdul Munir; Hartono, Arif; Muafi, Muafi (Jurnal Manajemen Bisnis, 2022)
Research aims: This study examines the process of member self-identification toward Al-Ma'un values as an organizational identity at PKU Muhammadiyah Yogyakarta Hospital.Design/Methodology/Approach: This study applied a qualitative case study method to obtain data, information, and knowledge related to members' awareness of Al-Ma'un, which was the source of inspiration for the birth of this hospital in 1923. Informants consisted of employees, with the primary data collection through in-depth interviews. Research findings: The study findings revealed that the member identification toward Al-Ma'un values has internalized into a nested identity, which becomes the organizational identity of PKU Muhammadiyah Yogyakarta Hospital. Theoretically, this study found a solid and long-standing distinctive value of the three CED criteria (central, enduring, and distinctive) in the organizational identity concept, as introduced by Albert and Whetten (1995), with Al-Ma'un as a unique feature distinguishing PKU Muhammadiyah Hospital from other hospitals. The facts also showed that there was still a value alignment since several services from some PKU Muhammadiyah Hospital health workers still have not shown consistent Islamic behavior.Theoretical contribution/Originality: This research theoretically contributes to the development of organizational theory related to religiosity organizational identity as a relatively new object of study using a qualitative approach in the discipline of economics. Findings of religiosity organizational identity based on the values of Al-Ma'un have the nature of novelty and originality of this research.Practitioner/Policy implication: This research has practical implications in the form of a new approach to developing hospital management based on religious values (Al-Ma'un) in dealing with the dynamics of social-humanitarian and non-profit orientations with professional and profit orientations. In addition, this research can be used for hospital development, which is coherent between a non-profit with professional orientation and profit orientation, which is still built on the organizational identity values.Research limitation/Implication: This study implies that a more robust internalization is needed to make Al-Ma'un a unique identity, image, and branding of the organizational identity of PKU Muhammadiyah Yogyakarta Hospital. The limitation of this research is that the case study was only in one Muhammadiyah hospital, so it is not to be generalized to other hospitals with different organizational backgrounds. Since it emphasizes the self-identification process related to knowledge, commitment, and action aspects in forming an organizational identity based on Al-Ma'un values, this study did not elaborate in-depth on the dynamic aspects of continuity and discontinuity processes from the identification process of these three aspects, which require further research to obtain a broader understanding of the problem under study.